Determination of Factor Xa Activity by Means of Chromogenic Substrates Based on the Primary Structure of Prothrombin - Aurell, L.; Olausson, A.; Claeson, G. (Thrombosis and Haemostasis, 1975)
Through the work of Magnusson and co-workers leading to the elucidation of the primary structure of prothrombin including the amino acid sequences around the two bonds split by factor Xa it has been possible to design a synthetic chromogenic peptide substrate. Bz-Ile-Glu-Gly-Arg-pNA, specifically intended for the determination of factor Xa. Furthermore, additional substrates have been synthezised with various alterations in the amino acid sequence. The activity of factor Xa and other serine proteases within the coagulation and fibrinolytic systems towards these substrates will be discussed with special regard to their possible use in coagulation studies.